Regional, socioeconomic and behavioural- impacts on consumer acceptability of beef in Northern Ireland, Republic of Ireland and Great Britain. (August 2019) - Chong, F.S.; Farmer, L.J.; Hagan, T.D.J.; Speers, J.S.; Sanderson, D.W.; Devlin, D.J.; Tollerton, I.J.; Gordon, A.W.; Methven, L.; Moloney, A.P.; Kerry, J.P.; O'Sullivan, M.G.
Abstract: This study was commissioned to assess if there are regional differences in the acceptability of beef between consumers from Northern Ireland (NI), Republic of Ireland (ROI) and Great Britain (GB). Palatability traits were affected by socioeconomic and behavioural factors such as preferred cooking endpoint, animal welfare, value, health aspects of beef product, ease of preparation as well as consumption frequency for specific cuts. "Willingness to pay" (WTP) was influenced by income, preferred cooking endpoint, value of beef product, ease of preparation and consumption frequency for frying steak. Results showed that GB consumers scored higher for the same striploin steak compared to NI and ROI consumers. This may be due to differences in the motivation for beef choice and/or consumption habits. GB consumers were less concerned about the healthiness of beef product and beef origin. In addition, a higher consumption frequency for rump was reported in GB, which may explain the higher sensory scores observed among GB consumers for striploins.